Jornalismo popular na era da comunicação digital : um estudo dos jornais Extra e Agora São Paulo - Filho, Antonio da Rocha e Silva (2018)
This research brings a study of the effects of digital communication in popular journalism practiced in Brazil. For that, Extra and Agora São Paulo newspapers were selected. These newspapers are published by two of the largest communication groups in the country (Globo and Folha), were born in print and represent the model of popular journalism based on service inaugurated in the later years 1990. Based on the concepts of popular journalism proposed by Márcia Franz Amaral and on-line journalism presented by Ramón Salaverría and João Canavilhas, the study initially discusses the importance of popular newspapers, their characteristics, the sensationalism that permeates the segment and the evolution of digital communication. The work brings an analysis of the homepages and social media Facebook and Twitter of the two newspapers, based on tools proposed by Marcos Palacios, and presents interviews with editors of the two media outlets to understand the editorial choices in the online environment and to know the impacts of the digital communication in the work of professionals in popular journalism. The results of the research indicate that Extra is at a more advanced stage of online journalism and has been using digital tools for journalistic production for a longer period of time. It offers multimedia and interactive content for its readers and has intense action in social networks. Agora has a production still focused on the printed platform and begins to crawl in the digital world. It presents a totally static site and its presence in social media is small. The two newspapers, however, keep present in the online medium the main news values of popular service journalism: entertainment, proximity and utility. The two vehicles are undergoing major transformation periods: Extra newsroom has been unified with O Globo newspaper, and Agora is preparing to launch a totally redesigned new website and to expand its activities in social media. The transformations bring new impacts to the two vehicles, which currently use different strategies in the digital environment. This work presents the performance of Extra and Agora in the online medium so far and the scenarios that each one lives in the moment, which should mean new modifications in each of them.